Effects of Incubation Temperature Variation on Embryonic Development Rate, Hatching time, Abnormality and Survival of Larval Sea Urchin Salmacis sphaeroides - Tri Nabila Putri; Muhammad Junaidi; Victor David Nico Gultom (Jurnal Biologi Tropis, 2026)
Salmacis sphaeroides is a species of sea urchin that plays an important role in economic and ecological aspects. However, high utilization rates by the public have led to a natural decline in population, This is provide a controlled environment that ensures a high-quality supply of sea urchin, reducing dependence on natural stocks. This study aims to analyze the effect of temperature differences on the rate of S. sphaeroides development, hatching rates, abnormality and survival rates of sea urchin embryo maintained by incubation of temperature, consisting of 5 treatments and 3 repeats. The method used in this research was an experimental method using the Complete Randomization Design. ANOVA tests showed that temperature had a significant effect on the hatch resistance, abnormality and survival of sea urchin larvae. Duncan continued testing. The results of research on embryonic development rates, hatching rate, abnormality and survival rates of sea urchins are significantly different. The best development and hatching rate is found at 28℃-30℃, the best abnormality at 28℃ with a value of 15.0±2.3 ᵃ and the best survival rate is also recorded at 28℃ with a value of 79.3±10.1 ᶜ. These results identify that temperatures of 28℃-29℃ can be recommended for sea urchin cultivation, taking into account the balance between egg hatches, abnormality and survival rate of sea urchin larvae.